2007
DOI: 10.1117/12.717483
|View full text |Cite
|
Sign up to set email alerts
|

Brightness increase in LED by recycling of light for projection applications

Abstract: A general theory on light-pipe/tunnel-based recycling schemes, along with some experimental data obtained from LED illuminators, is presented in this paper. Light recycling is classified as angular, spatial, or mixed based on the angular filtering characteristics of the recycling process. The principles behind the three schemes are analyzed and some experimental results are presented at the end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The case for mixed recycling is more complicated as both angular and spatial recycling is at work. However, it can be shown that with some simplifying assumptions we can arrive at the same power flow diagram [3]:…”
Section: Mixed Recyclingmentioning
confidence: 99%
“…The case for mixed recycling is more complicated as both angular and spatial recycling is at work. However, it can be shown that with some simplifying assumptions we can arrive at the same power flow diagram [3]:…”
Section: Mixed Recyclingmentioning
confidence: 99%
“…The etendue reduction ratio is the ratio of the total area of the output aperture over that of the uncoated window. The principle of enhancing brightness through light recycling has been explained in our previous work 5,6 . For the specific DPR system described above (output etendue = 50 mm 2 *steradian) and with a 4:1 etendue reduction ratio (recycling light pipe etendue = 200 mm 2 *steradian), simulation has shown that 40% of total lumen gain has been achieved.…”
Section: Fig 6 Output Aperture Of the Recycling Light Pipementioning
confidence: 99%
“…It can be shown that if one considers light recycling in LED chips, then the extracted light increases with respect to the case in which is disregarded [15,16]. Light recycling can also considerably increase the brightness of LEDs [34,35]. This denotes the importance of both an analysis of light recycling, and a good design of the mirror cup.…”
Section: A Flat Chipmentioning
confidence: 99%